On-line screening of natural antioxidants and the antioxidant activity prediction for the extracts from flowers of Chrysanthemum morifolium ramat. (10th August 2022) - Zhang, Zhiyong; Zhang, Yazhong; Wang, Long; Cui, Tongcan; Wang, Yuxin; Chen, Junhui; Li, Wenlong
Abstract: Ethnopharmacology relevance: Chrysanthemum morifolium Ramat. (Flos Chrysanthemi, FC) the most economically significant "food and drug dual-use" plants, with positive effects on relieving eye fatigue, and reduce internal heat, shows significant activities, such as anti-inflammatory, antioxidant, and neuroprotective, as well as alleviating diabetes effects. Aim of the study: This study was undertaken to a screening of natural antioxidants in five kinds of medicinal FC and development of an integrated quality control method based on the antioxidant activity. Materials and methods: A novel quality control method for FC was established by combining the on-line HPLC-DPPH, ESI-MS, and NIR spectra analysis. Firstly, the on-line HPLC-DPPH-MS system was employed to identify the antioxidants in FC extracts. Then, the relationship between the NIR spectra and antioxidant activities of FC samples was calibrated to evaluate the total antioxidant capacity of FC rapidly. Results: The established antioxidant activity-fingerprints contain both chemical information and antioxidant activity characteristics of FC. A total of 16 antioxidants were identified by on-line HPLC-ESI-MS analysis. The results of heat map analysis and cluster analysis showed that the classification method based on antioxidants in FC can be used to identify different cultivars of FC. The optimal pretreatment of the NIR spectra was determined to be row center (RC) 1st der + multiple-scatter correction (MSC) with an optimal LV value of 11. The developed spectral-antioxidant activity model had the excellent predictive ability and was successfully used to evaluate new batches of FC samples, where R cal  = 0.9445 and R val  = 0.8821. Conclusions: This comprehensive strategy may prove to be a powerful technique for the rapid screening, identification, and activity prediction of antioxidants, which could be used for the quality control of FC, and can serve as reference for design of quality control of other herbs and foods samples. Graphical abstract: Image 1 Highlights: Determination of optimum experimental conditions for on-line HPLC-DPPH assay with response surface methodology. Analysis and identification of antioxidants in FC using HPLC-ESI-MS analytical technology. Developing an integrated quality evaluation method for the antioxidant activity-fingerprint of five kinds of medicinal FC . NIR spectroscopy based calibration model was established for the prediction of the antioxidant activities of FC samples.